BMP Signaling in the Development and Regeneration of Cranium Bones and Maintenance of Calvarial Stem Cells - Chen, Guiqian; Xu, Haodong; Yao, Yifeng; Xu, Tingting; Yuan, Mengting; Zhang, Xingen; Lv, Zhengbing; Wu, Mengrui (Frontiers in Cell and Developmental Biology, 2020)
The bone morphogenetic protein (BMP) signaling pathway is highly conserved across many species, and its importance for the patterning of the skeletal system has been demonstrated. A disrupted BMP signaling pathway results in severe skeletal defects. Murine calvaria has been identified to have dual-tissue origins, namely, the cranial neural-crest cells and the paraxial mesoderm. Modulations of the BMP signaling pathway have been demonstrated to be significant in determining calvarial osteogenic potentials and ossification in vitro and in vivo. More importantly, the BMP signaling pathway plays a role in the maintenance of the homeostasis of the calvarial stem cells, indicating a potential clinic significance in calvarial bone and in expediting regeneration. Following the inherent evidence of BMP signaling in craniofacial biology, we summarize recent discoveries relating to BMP signaling in the development of calvarial structures, functions of the suture stem cells and their niche and regeneration. This review will not only provide a better understanding of BMP signaling in cranial biology, but also exhibit the molecular targets of BMP signaling that possess clinical potential for tissue regeneration.